2008
DOI: 10.1186/1750-1326-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Detergent resistant membrane-associated IDE in brain tissue and cultured cells: Relevance to Aβ and insulin degradation

Abstract: BackgroundInsulin degrading enzyme (IDE) is implicated in the regulation of amyloid β (Aβ) steady-state levels in the brain, and its deficient expression and/or activity may be a risk factor in sporadic Alzheimer's disease (AD). Although IDE sub-cellular localization has been well studied, the compartments relevant to Aβ degradation remain to be determined.ResultsOur results of live immunofluorescence, immuno gold electron-microscopy and gradient fractionation concurred to the demonstration that endogenous IDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 58 publications
6
34
0
Order By: Relevance
“…An association of IDE with endosomes and detergent-resistant membrane microdomains, which are enriched in endosomal compartments, has been reported recently (61). MVBs are intrinsic components of the endosomal system and formed by the inward budding of endosomal membranes (38,40).…”
Section: Discussionmentioning
confidence: 89%
“…An association of IDE with endosomes and detergent-resistant membrane microdomains, which are enriched in endosomal compartments, has been reported recently (61). MVBs are intrinsic components of the endosomal system and formed by the inward budding of endosomal membranes (38,40).…”
Section: Discussionmentioning
confidence: 89%
“…3A). It has been reported that there are two pools of IDE: a cytosolic pool with a longer half-life and a plasma membrane pool that shows faster turn-over [54]. The membrane-bound IDE protein level is important because its level is related to the clearance of A␤ plaques in A␤PP transgenic mice [55] and its decrease in the brain of individuals is associated with a high risk of developing AD [56].…”
Section: Discussionmentioning
confidence: 99%
“…These include insulin, glucagon, and insulin-like growth factors I and II, and IDE also converts β-endorphin to γ-endorphin [130, 131]. Interestingly, the enzyme does not contain an obvious signal sequence and is mostly intracellular, yet reports suggest that IDE, in neurons, may be membrane-associated and even secreted into the medium [132, 133]. However, it remains unclear whether IDE is secreted or simply released from damaged cells.…”
Section: Other Pathways For Aβ Turnovermentioning
confidence: 99%